A pickup and delivery problem for ridesharing considering congestion. Issue 5 (19th October 2016) - Wang, X.; Dessouky, M.; Ordonez, F.
Abstract : Traffic congestion is a significant social concern that is credited with considerable economic costs, wasted time, and associated public health risks. Efficient ridesharing solutions could help mitigate congestion. Some of the actions that government agencies have taken to encourage ridesharing include the availability of high occupancy vehicle (HOV) lanes and existing policies of discounted toll rates on HOVs. These measures encourage ridesharing by reducing costs or travel times of such trips. To study how the optimal routes change as a function of incentives for ridesharing, we modified existing pickup and delivery problems with time windows to consider changes in passenger travel time and toll cost due to vehicle load. Our computational results explore how the total route cost and time are affected by the use of HOV lanes and toll savings. In addition, our results show that it can be beneficial from a time and cost perspective to take detours to pick up additional passengers and use HOV lanes when the time saving on HOV lanes is significant.